Translator Training in Jamaica: Modest Output for a New Outlook - Preston, Doreen (Meta, 1998)
AbstractThis article gives a brief overview of translator training in Jamaica and presents the principal characteristics of the M.A. programme currently offered at the Mona campus of the University of the West Indies in Jamaica.